A oikonomia da universidade filantrópica e o dom do desenvolvimento sustentável - Forneck, Romeu (Universidade do Vale do Rio dos Sinos, 2016)
In this paper, we will find elements with which the author tries to express his comprehension about the development theme, suggesting the university as an alternative for the promotion of the sustainable social development. We are at a historical moment in which it looks like marginal effects of the action or of the human evolution are being manifested over its own pre-conditionings of preservation. Therefore, it seems as this action had an influence of an instinct of natural evolution in its dynamics. As part of the universe, we humans dislocate in time, with different social speeds, displacing us relatively and sparsely from the origin, consuming energies according to the stage of the different dislocations. Endowed with imperative reason, we create associations that reproduce our natural or social linkages, in whose cradle we try to protect ourselves while being creatures naturally fragile. Those associations or economic institutions that are generated from space-time, social experiences of exchange (exemplified in archaic societies, in the church or in the State), at the same time that they comply with the natural demand for protection or social welfare, establish objective mechanisms for the preservation of the social differences. In order to put that phenomenon in context, this paper discusses on topics such as: the evolution and nature of things; the social organization and power structure; capitalism; the State; religions and church; ethic and the institutions. Moreover, the author tries to put back in context the idea of development, creating approaches applied to the concepts of economy, development and sustainable development. Considering that the main object of study is based on the evaluation of the effects of the different kinds of relations at the University of Vale do Rio dos Sinos (UNISINOS) on its various demands, the author analyses the context of the social-economic constitution in Brazil, highlighting two South-Brazilian projects (the Guarani Missions, and the German Immigration in South Brazil), projects for new and differentiated offerings, which led to social equity of those involved. From the analysis of historical motivations of the development, sorting the development of different cultures, the role of the various ways of organizing and thinking about development, the relationship between the income and the 1,478,487 semester grades of these students (1990 – 2007), are believed to have found evidence to shows that: a) the development is human and is different from evolution; b) the exogenous variables of consciousness, such as the force of nature, or the dynamics of social income, seem to be in the causality of the motivations of initiatives and economic development; c) equity and sustainable development result from endogenous offers; d) if the University organizes itself and offers itself as a community with a view to the search for the truth, integrating the differentiated society in this quest, it will be promoting freedom and social equity, a priori conditions for sustainable development; e) when the university fails to understand the demands of less privileged socio-economic contexts as a passive field for the internship and social assistance, and prioritize the inclusion of members of these contexts, with its rich experiences, in the community of discoveries of the University, will be generating a Transformative and liberating action for the contexts of these demands.
Keywords: Evolução; Desenvolvimento; Universidade; Verdade; Ética; Liberdade; Desenvolvimento sustentável; Evolution; Development; University; Truth; Ethics; Freedom; Sustainable development; ACCNPQ::Ciências Humanas::Sociologia